THE ROLE OF TEACHERS IN CREATING CHILD-FRIENDLY SCHOOLS AT MURHUM KINDERGARTEN - Ermina Pratiwi; Rachman Saleh; Hartati Hartati (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to analyze the role of teachers in creating child-friendly schools at Murhum Kindergarten, especially their role as motivators and role models for children. A child-friendly school is an educational environment that ensures children’s rights, safety, comfort, participation, and optimal development during the learning process. Teachers play an important role in creating a positive and supportive atmosphere that helps children develop socially, emotionally, and academically.This research used a qualitative descriptive method with observation, interviews, and documentation as data collection techniques. The participants included teachers and the principal of Murhum Kindergarten. The findings show that teachers contribute significantly to implementing child-friendly school principles through caring interactions, positive communication, enjoyable learning methods, and non-violent discipline. As motivators, teachers encourage children to participate actively, build self-confidence, and develop enthusiasm for learning through appreciation and emotional support. As role models, teachers demonstrate discipline, honesty, politeness, responsibility, and empathy, which influence children’s behavior positively. The study concludes that teachers have a central role in realizing child-friendly schools at Murhum Kindergarten through their functions as educators, motivators, and role models.